Analisis Kebutuhan Air Irigasi Daerah Aliran Sungai Durslin Kabupaten Lingga - Suci Amalia; Manyuk Fauzi; Yohanna Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2022)
The Durslin Watershed is one of the watersheds located on Singkep Island, Lingga Regency, Riau Islands Province with an area of 99.80 km2. In accordance with Permen PUPR (2018), the Lingga Regency River Area is in the medium-critical zone. However, the local government plans to increase the irrigation areas as the highest contributor to the economy. The expansion of the irrigation area must be supported by an adequate water supply. So it is necessary to conduct research related to the irrigation water demand in the Durslin watershed. The method for determining evapotranspiration is using Penman-Monteith with calculations based on the KP-01. The analysis is then projected for the next twenty years to 2040. Result the research show that the demand for irrigation water is always increasing every year. In 2021 irrigation water demand is 0.1022 m3/sec, while irrigation water demand in 2040 is 0.2922 m3/sec.Keywords: irrigation, watershed, water demand